Decolonial Feminist Community Psychology: Centering the Margins - Ravn, Amalie (PINS-Psychology in Society, 2019)
[BOOK REVIEW] Boonzaier, Floretta & van Niekerk, Taryn (eds.) (2019) Decolonial feminist community psychology, 1st edition. Switzerland: Springer. ISBN-10: 3030200000 ISBN-13: 978-3030200008 Pages 160 Decolonial feminist community psychology is a recent and emerging form of psychology. As a sub-discipline in the field, community psychology – the applied study of the relationship between social systems and individual well-being in the context of community (Hanlin et al., 2008, p. 524) – dates back only around 50 years. Decolonial Feminist Community Psychology, edited by Floretta Boonzaier and Taryn van Niekerk, takes these efforts one step further by advancing a concerted investigation of the relationship between decolonial and feminist approaches within community psychology. This volume critically engages with and develops feminist and anticolonial voices from the global south as protest against hegemonic and Northern knowledge. The contributors to the book were encouraged to assist the editors in envisioning an emerging decolonial and feminist community psychology. The editors remark that ‘such a form of psychology already exists.’ This statement – that this work is already here and remains ongoing – is amply illustrated throughout the volume.